Diuretic activity of the aqueous crude extract and solvent fractions of the leaves of Thymus serrulatus in mice - Melka AE; Makonnen E; Debella A; Fekadu N; Geleta B (Dove Medical Press, 2016)
Amelework Eshetu Melka,1 Eyasu Makonnen,1 Asfaw Debella,2 Netsanet Fekadu,2 Bekesho Geleta2 1Department of Pharmacology, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Directorate of Traditional and Modern Medicine Research, Ethiopian Public Health Institute, Addis Ababa, Ethiopia Abstract: The present study was undertaken to investigate the diuretic activity and acute toxicity profile of the crude aqueous extract and solvent fraction of the leaves of Thymus serrulatus in saline-loaded Swiss albino mice. Mice of either sex were divided into six groups (five animals in each group). The control group received normal saline (25 mL/kg), while the reference group received hydrochlorothiazide (10 mg/kg). Group III to Group VI received the test substances at dose levels of 125, 250, 500, and 1,000 mg/kg orally, respectively. At the end of the fifth hour, urine was collected, and total volume of urine excreted by each animal was recorded. Concentrations of urinary Na+ and K+ were determined, and the Na+/K+ ratio was calculated to make comparison among the groups. The acute toxicity of the most active fraction was also evaluated. The findings demonstrated that the crude aqueous extract of T. serrulatus leaves showed significant diuretic (P<0.01), natriuretic (P<0.01), and kaliuretic (P<0.01) effects. At the dose of 1,000 mg/kg, the n-butanol fraction demonstrated the highest diuretic activity comparable to the reference drug. It also showed a good natriuretic activity. The dichloromethane fraction, however, did not have significant diuretic activity. Both the crude aqueous extract of the leaves of T. serrulatus and its n-butanol fraction have diuretic activity with high concentration of urinary electrolytes in mice. Further studies, however, need to be pursued on the possible mechanism(s) of diuretic action. Keywords: Thymus serrulatus, diuretic activity, electrolyte excretion, Na+/K+ ratio